2017
DOI: 10.1016/j.aller.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of a pattern of exhaled breath condensate biomarkers in asthmatic children

Abstract: An approach that involves a pattern of EBC biomarkers had a better diagnostic accuracy for asthma in children in real-life settings compared to a single one. Poor to moderate association of EBC biomarkers with lung function suggests a complementary value of EBC analysis for asthma diagnosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Comparable results were observed in EBC collected from 22 healthy children and 17 asthmatics with the latter having a statistically significantly lower iron concentration (55). Another study with a small number of participants observed no significant differences in EBC iron concentration between asthmatics (n= 10) and non-asthmatics (n=16) (62). Using a “bleomycin technique for measurement of pro-oxidant iron”, there was an increase in EBC iron levels post-exposure to city environments among severe asthmatics (60).…”
Section: Metals In Ebc In Diseased Populationsmentioning
confidence: 96%
“…Comparable results were observed in EBC collected from 22 healthy children and 17 asthmatics with the latter having a statistically significantly lower iron concentration (55). Another study with a small number of participants observed no significant differences in EBC iron concentration between asthmatics (n= 10) and non-asthmatics (n=16) (62). Using a “bleomycin technique for measurement of pro-oxidant iron”, there was an increase in EBC iron levels post-exposure to city environments among severe asthmatics (60).…”
Section: Metals In Ebc In Diseased Populationsmentioning
confidence: 96%
“…With respect to asthma control, pH was significantly decreased in a group of children with uncontrolled asthma as defined by GINA guidelines (21). However, in other recent studies, no significant difference in EBC pH was found between asthmatic and non-asthmatic children, nor between atopic and non-atopic asthma (20, 28). Nonetheless, sample sizes from both studies were small.…”
Section: Findings From Cross-sectional Studiesmentioning
confidence: 60%
“…Although the aforementioned studies show intriguing findings, they should still be considered as part of a new or ongoing pilot project in which a single marker or analytical method is tested on EBC. Only one recent cross-sectional study tried to create a discriminative model using different EBC markers (20). In this study, a significant predictive model for asthma was created using six different biomarkers: pH, pCO 2 , pO 2 , magnesium, calcium, and urates (20).…”
Section: Findings From Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation